FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI ROTI KOMPIANG (STUDI KASUS PADA TOKO TARZAN DI RUTENG KABUPATENMANGGARAI) - Mersiana Dadung; Herman Jelatu; Marselinus Jewaru (Jurnal Humaniora & Sosial Sains, 2024)
This study aims to determine the direct and simultaneous influence of capital, labor, raw materials on the production of kompiang bread at the Tarzan shop in Ruteng, Manggarai Regency, East Nusa Tenggara. This study uses a quantitative approach, using a descriptive analysis method. The population in this study was 300 employees and the sampling technique used Sugiyono's theory with a sample of 45 employees. The data collection method used interviews, questionnaires and documentation. The data were analyzed using multiple linear regression analysis, partial tests, simultaneous tests and coefficient of determination (R2). Based on the multiple linear regression model obtained the results of the analysis are Y = 40.356 + 0.386X1 + 0.387X2 + 0.066X3. It is known that capital, labor, raw materials have a partial (positive) effect on the production of kompiang bread at the Tarzan shop in Ruteng, Manggarai Regency. where the t-count value is greater than the t-table including capital (2.762 > 1.683), labor (2.511 > 1.683), raw materials (1.831 > 1.683) and the results of the simultaneous test show that the F-count is greater than the F-table (4.438 > 2.83), meaning that capital, labor, raw materials have a simultaneous effect on the production of kompiang bread at the Tarzan shop in Manggarai Regency.